Feeding Japan : The Cultural and Political Issues of Dependency and Risk - Niehaus, Andreas; Walravens, Tine (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This edited collection explores the historical dimensions, cultural practices, socio-economic mechanisms and political agendas that shape the notion of a national cuisine inside and outside of Japan. Japanese food is often perceived as pure, natural, healthy and timeless, and these words not only fuel a hype surrounding Japanese food and lifestyle worldwide, but also a domestic retro-movement that finds health and authenticity in 'traditional' ingredients, dishes and foodways. The authors in this volume bring together research from the fields of history, cultural and religious studies, food studies as well as political science and international relations, and aim to shed light on relevant aspects of culinary nationalism in Japan while unearthing the underlying patterns and processes in the construction of food identities.